Hubungan Derajat Hipertensi dengan Kecemasan di Klinik Pratama Biddokkes Polda Jawa Barat Tahun 2024 - Rifki, Muhammad Hikmal; Akbar, Ieva Baniasih; Widayanti (UPT Publikasi Ilmiah Unisba, 2025)
Abstract. Hypertension, a global health threat, frequently coexists with anxiety, yet specific data on this association in local, high-stress populations are limited. This study aimed to analyze the relationship between hypertension grade and anxiety among patients at the Pratama Biddokkes Clinic of the West Java Regional Police. Employing an observational cross-sectional design, the study included 88 adult hypertensive patients (aged 30–69 years) with a normal body mass index; data was collected during November–December 2024. Hypertension was classified as grade 1 or 2, and anxiety was quantitatively measured using the Hamilton Anxiety Rating Scale (HARS). The relationship's strength and risk were analyzed using the Gamma test and Odds Ratio (OR). Results showed a majority of respondents had grade 2 hypertension (74%) and experienced anxiety (64%). A significant relationship was confirmed via chi-square analysis (p = 0.025). The Gamma test yielded a coefficient of +0.518, indicating a positive, moderate-strength relationship. Patients with grade 2 hypertension were 3.14 times more likely to experience anxiety (OR = 3.14). In conclusion, a significant, positive, and moderately strong relationship exists between hypertension grade and anxiety. A higher hypertension grade increases the likelihood of anxiety, emphasizing the critical importance of screening and managing anxiety as part of holistic care to improve treatment outcomes. Abstrak. Hipertensi sering disertai kecemasan, namun bukti mengenai hubungan keduanya pada populasi dengan tingkat stres tinggi masih terbatas. Penelitian ini bertujuan menganalisis hubungan antara derajat hipertensi dan kecemasan pada pasien di Klinik Pratama Biddokkes Polda Jawa Barat. Studi observasional cross-sectional ini melibatkan 88 pasien hipertensi dewasa berusia 30–69 tahun dengan indeks massa tubuh normal. Data dikumpulkan pada November–Desember 2024. Derajat hipertensi diklasifikasikan menjadi derajat 1 dan derajat 2, sementara kecemasan dinilai menggunakan Hamilton Anxiety Rating Scale (HARS). Analisis dilakukan melalui uji chi-square, Gamma, dan Odds Ratio (OR). Hasil menunjukkan sebagian besar responden mengalami hipertensi derajat 2 (74%) dan kecemasan (64%). Ditemukan hubungan signifikan antara derajat hipertensi dan kecemasan (p = 0,025). Koefisien Gamma +0,518 menunjukkan hubungan positif berkekuatan moderat. Pasien dengan hipertensi derajat 2 memiliki risiko 3,14 kali lebih tinggi mengalami kecemasan (OR = 3,14). Penelitian ini menegaskan bahwa peningkatan derajat hipertensi berhubungan dengan meningkatnya kecemasan, sehingga skrining dan penanganan kecemasan perlu menjadi bagian dari pendekatan perawatan yang komprehensif.